PARTICIPATION AND WAGE OF RURAL FEMALE HEADED HOUSEHOLDS IN NIGERIA NON-FARM EMPLOYMENT - Idowu, Adewunmi O.; Ojiako, Ifeanyi A.; Ambali, Omotoyole I. (European Scientific Journal, ESJ, 2013)
Considering the growing importance of rural development diversifying income through the non-farm activities in complementing proceeds of agricultural development, the study determines the rural female headed farm households’ participation and wage in non-farm activities. Data were analyzed using descriptive statistics, Herfindal index, Probit, Tobit and Heckman two-step regressions. Average rural female headed farm household consist of seven members with income diversification level of 2.8. Education, dependency ratio and distance to the urban centres determined the household participation in non-farm activities while wages receive in non-farm employment were determined by hour of labour supplied, distance to the urban centres, and education.